IMPLEMENTATION GUARANTEE HEALTH FOR OFFICER AD HOC IN IMPLEMENTATION SIMULTANEOUS GENERAL ELECTIONS REVIEWED FROM THE PERSPECTIVE OF SOCIOLOGY OF LAW - Ariel Patrick Raphello; Catharina Dewi Wulansari (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Indonesia holds a democratic celebration, namely general elections, every four years. Indonesia held its first simultaneous general elections in 2019. The 2019 Simultaneous General Elections apparently had an impact. health to the ad hoc committee and supervisors assigned to the Simultaneous General Election, as many as 840 member KPPS die world And 11,239 member KPPS experiencing pain. Many member KPPS Which die world due to height burden Work During the 2019 Simultaneous General Elections, excessive working hours resulted in mass fatigue, leading to unavoidable health impacts, including illness and even death. Legislation governing elections and regional elections currently does not regulate health insurance for ad hoc committee members and supervisors. The election organizers have proposed health insurance for ad hoc committee members and supervisors, but it has not yet been approved. Currently, the Ministry of Finance issued Letter No. S-647/MK.02/2022, dated August 5, 2022, concerning Other Input Cost Units (SBML) for General Election Stages. And Stages Election, However Letter Ministry Finance Law Number S-647/MK.02/2022 focuses solely on occupational accident insurance, while occupational accident insurance regulates a different subject than health insurance. This study aims to propose a concept regarding health insurance for the committee and supervisors of the 2024 simultaneous general and regional head elections, supported by a normative legal research method with a sociological approach.